Diseño Y Aplicación Del Programa De Conservación Auditiva Para La Prevención De Alteraciones De Los Trabajadores Expuestos A Ruido En La Empresa Pública De Hidrocarburos Del Ecuador - Marco Hjalmar Velasco Arellano; Carla Sofía Arguello Guadalupe; José Franklin Arcos Torres; Patricia del Lourdes Gallegos Murillo; Andrea Patricia Guapi Auquillas (European Scientific Journal, ESJ, 2017)
Shushufindi field is located in the Amazon basin, between the meridians 76 and 77, and the Equinoccial line parallel South. It is oriented in the North-South direction, with approximately 35 Km, from long and 7 Km wide, covering an area of about 200 square km. This paper establishes the design and implementation of the programme of hearing conservation for the prevention of disorders of workers occupationally exposed to noise in the field Shushufindi of EPP, developed for workers who are dedicated to activities in the areas of heavy equipment and turbine; establishing the risk factors that may affect health and well-being, allows to implement prevention and protection controls, so workers can carry out their activities in a proper workplace. To carry out the work we performed a literature review and risk factor was identified through the use of a matrix, noise to which workers are exposed, with the use of the method of the three-step (PGV) was carried out the estimation of the risk; determined that the risk of noise value corresponds to 9 considered an intolerable risk, this allowed their preventive management. Hearing conservation program implemented in a systematic way to protect hearing from employees, allows you to prevent the health effects, reduce labor absenteeism, improve industrial productivity, and improve the working conditions of the company.